THE INTONATION OF RHETORICAL QUESTIONS IN ITALIAN (ItalianoLinguadue, 2023)
This research focuses on the intonation of rhetorical questions (RQs) in Italian. RQs are non-prototypical questions characterised by specific pragmatic features such as indirect and obvious meaning and the absence of an informative answer. The basic idea is that prosody, in its various verbal and paraverbal components, provides listeners with cues of illocutionary interpretation of RQs, facilitating their recognition in spontaneous speech. Although in the past the presence of a final falling intonation contour was assumed as a categorical feature of RQs, recent studies showed a more heterogeneous situation which did not exclude the possibility of rising intonation contours. Most of these studies were conducted on elicited speech samples (DCT or Role Play) by directly comparing string-identical information-seeking questions with rhetorical questions. The results obtained in several languages show that the differences between the two question types are never clear-cut and do not equally involve the same prosodic parameters (intonation contour, pitch range, duration). This highlights the presence of language-specific components. However, it is possible that the final results might have been influenced by both the mode of acquisition of the speech samples (which were almost always collected in a controlled environment), and by a certain neutralisation of discursive functions. The present research analyses a corpus of 100 spontaneous oral wh-RQs extracted from radio broadcasts. The study presents a phonological analysis of the intonation of RQs, looking at nuclear pitch accents and boundary tones. The results are then compared with those previously obtained for the same geographical area. L’intonazione delle domande retoriche in italianoQuesta ricerca si concentra sull’intonazione delle domande retoriche (RQ) in italiano. Si tratta di domande non prototipiche caratterizzate da specifiche caratteristiche pragmatiche, tra cui la presenza di un significato indiretto e ovvio e l’assenza di una risposta informativa. L’idea di base è che la prosodia, nelle sue varie componenti verbali e paraverbali, fornisca agli ascoltatori degli indizi di interpretazione illocutiva delle RQ, facilitandone il riconoscimento nel parlato spontaneo. Sebbene in passato la presenza di un contorno intonativo discendente finale sia stata assunto come una caratteristica categorica delle RQ, studi recenti hanno mostrato una situazione più eterogenea che non esclude la possibilità di contorni intonativi ascendenti. La maggior parte di questi studi è stata condotta su campioni di parlato elicitato (DCT o Role Play), confrontando direttamente coppie frasali identiche formate da domande sincere e domande retoriche. I risultati ottenuti in diverse lingue mostrano che le differenze tra i due tipi di domanda non sono mai nette e non coinvolgono in egual misura i medesimi parametri prosodici (contorno intonativo, pitch range e durata), evidenziando la presenza di componenti linguo-specifiche. Tuttavia, è possibile che i risultati finali siano stati influenzati dalla modalità di acquisizione dei campioni di parlato (quasi sempre raccolti in un ambiente controllato) e da una certa neutralizzazione delle funzioni discorsive. La presente ricerca analizza un corpus di parlato spontaneo formato da 100 domande retoriche con struttura wh- estratte da trasmissioni radiofoniche. Lo studio fornisce un’analisi fonologica dell’intonazione delle domande, focalizzandosi sugli accenti intonativi nucleari e sui toni di confine. I risultati sono stati successivamente comparati con quelli precedentemente ottenuti per la stessa area geografica.